Demographic and clinical profile of chronic rhinosinusitis patients in a rural based tertiary hospital - Garg, Deepika; Kamble, Ajay; Puttewar, Manish (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Chronic rhinosinusitis (CRS) is one of the most common health problems which incurs significant medical costs and has severe impact on lower airway diseases and general health of the patient. The aim of this study was to describe the demographic and clinical profile of chronic rhinosinusitis patients. Methods: In this study 94 patients were included. After taking a brief history, their clinical symptoms were assessed using SNSG test (sino nasal symptom grading test). The findings were further confirmed by diagnostic nasal endoscopy. Results: We found that maximum number of patients were in the age group of 18-27 years with a slight male preponderance. Also rural population had more cases of CRS with nasal discharge being the commonest complaint at the time of presentation. After diagnostic nasal endoscopy (DNE) it was found that ethmoidal polyps are more common in CRS patients however more number of CRS patients presented without polyps. Conclusions: We conclude that chronic rhinosinusitis manifests more in male and rural population with nasal discharge and ethomoidal polyps being the most common presentation. The subjective assessment of clinical symptoms could be done by SNSG test; however it further requires detailed studies.